Habitat selection, prescribed burn effects, and passive monitoring of Eastern black rails (Laterallus jamaicensis jamaicensis) in North Carolina - Kephart, Bailey A (East Carolina University)
Eastern black rail (Laterallus jamaicensis jamaicensis) populations have experienced rapid declines from habitat loss exacerbated by sea level rise and human development. The suitable habitat for this species is broadly described as marsh containing dense, herbaceous vegetation at high elevations with little to no standing water (~ 0-5 cm). However, habitat characteristics, such as vegetation species composition and hydrology, vary by location where black rails are found. In North Carolina, birds are concentrated in only a few areas of coastal marsh that are subject to erosion and likely to be lost within the century. Additionally, this species' behavior and phenology is poorly understood. As the black rail faces threats of extinction, it has become increasingly vital to better understand the species' activity patterns and identify viable management strategies to facilitate marsh migration away from the shoreline and preserve existing populations. Prescribed fire may be a useful tool for maintaining patches at an early-successional state and promoting quality habitat, but its effectiveness has not yet been assessed for the mid-Atlantic coastal plain. In Chapter 1, I identify and discuss characteristics of suitable habitat as they relate to burn management and the probability of black rail occupancy. I conducted callback surveys during the breeding season at sites that were either burned in mid-winter or left unburned in 2022. I created occupancy models to identify predictors of suitable habitat. In separate analyses, I directly compared these variables among sites left unburned, within one year of burn, and one-year post-burn. These results were then integrated to assess the effects of prescribed fire management on black rail habitat and the effect of burn status on habitat use. In Chapter 2, I uncover temporal patterns of vocal activity and propose a phenological timeline for black rails in coastal North Carolina. I used passive monitoring techniques to document aspects of phenology and behavior during the breeding season. During 2023, I deployed recording units and monitored water levels at Cedar Island NWR. Lunar illumination values were extracted for each hour that was recorded. Counts of verified detections (3-second segments of recordings of black rail vocalizations) were then incorporated into models that identified temporal predictors of 1) vocalization probability and 2) counts of call segments during active periods. Predictors of vocalization probability were assessed separately from estimated counts. Over the 2-year period, I deployed motion-activated trail cameras at locations where black rails were detected to uncover evidence of phenology and breeding activity. I captured evidence of a presumed immature black rail after the completion of its juvenile molt. This 2022 observation is the first record of confirmed breeding by black rails in North Carolina in over 120 years. Results of this project provide insights into habitat preferences, vocalization patterns, and breeding phenology of Eastern black rails in North Carolina.
Keywords: Eastern black rail; passive acoustic monitoring; occupancy model; single-season occupancy model; trail cameras; ARU; prescribed fire management; management; marsh bird; secretive; Autonomous Recording Unit; circadian activity; breeding phenology; vocal activity; habitat use; Black rail--North Carolina; Habitat selection--North Carolina; Endangered species--North Carolina; Prescribed burning--North Carolina; Wildlife conservation--North Carolina; Circadian rhythms